Konsep Pendidikan Tauhid Anak Menurut Abdullah Nashih Ulwan - Ika Sofia; Ahmad Zuhdi; Ngatoillah Linnaja (Student Scientific Creativity Journal, 2024)
. Abdullah Nashih Ulwan is one of the figures of Islamic education who pay great attention to children's education, through his books Tarbiyatul Aulad Fil Islam he explained the concept of monotheism education for children, the many cases of deviations from Islamic law committed by teenagers. This research aims to provide special knowledge to educators regarding monotheism education materials as well as educational methods. This research method is library research or literature and data analysis using content analysis methods. The results obtained are material for children's monotheistic education including: introducing the oneness of Allah SWT, instilling devotion to the power and supervision of Allah SWT, introducing Rasulullah SAW and teaching them to read the Qur'an and Islamic law. It is hoped that educators will understand the concept of providing monotheism education to children and be able to implement it.